Sudden cardiac death after acute myocarditis with arrhythmic presentation: hunting for risk predictors − a systematic review and meta-analysis - Massimo Imazio; Valentino Collini; Maria Lucia Narducci; Federico Ballacci; Federica Giordano (Open Heart)
Background Ventricular arrhythmias (VAs) frequently occur in the acute phase of myocarditis. Possible arrhythmic recurrences and the risk of sudden cardiac death (SCD) in this setting are reasons for concern, and limited data have been published to guide clinical management of these patients. The aim of the present paper is to report the incidence of major arrhythmic events, defined as sustained VA, SCD and appropriate implantable cardiac-defibrillator (ICD) treatment, in patients with acute myocarditis and ventricular arrhythmic phenotype.Methods We conducted a systematic review and meta-analysis following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to evaluate studies reporting long-term outcomes in patients with acute myocarditis and arrhythmic presentation. We systematically searched PubMed, EMBASE and Scopus databases for relevant studies up to 2 August 2024. Study quality was assessed by the Newcastle-Ottawa Scale. The primary outcome was a composite of SCD, VA recurrence and appropriate ICD therapy. Random-effect models were used to calculate pooled ORs and CIs.Results Five observational studies enrolling 322 patients were identified. The pooled proportion of patients who experienced VA recurrence was 0.41 (95% CI 0.30 to 0.53, p=0.13). An increased risk of adverse outcomes during follow-up was observed in patients presenting with monomorphic ventricular tachycardia (OR 3.77, 95% CI 1.23 to 11.53) and left ventricular ejection fraction (LVEF) <50% (OR 2.74, 95% CI 0.78 to 9.63). Gender and anteroseptal late gadolinium enhancement were not found as potential risk factors in this analysis.Conclusions Patients with myocarditis with arrhythmic ventricular presentation have a high recurrence rate of VA, underscoring the importance of careful monitoring and management in this patient population. Risk stratification for SCD during follow-up should be individualised, and monomorphic VA at presentation or a reduced LVEF may be markers of poor prognosis. In these cases, an ICD implantation may be cautious pending further dedicated studies.